Alginate-edible coatings for application on wild andean blueberries (Vaccinium meridionale swartz): Effect of the addition of nanofibrils isolated from cocoa by-products - Medina Jaramillo, Carolina (2020)
Edible coatings and films are appealing strategies for the postharvest management of blueberries. In the current work, alginate and alginate/cellulose nanofibril (CNF) edible coatings crosslinked with calcium chloride were developed for application on Andean blueberry (a promissory wild blueberry). Cocoa by-products were valorized through the isolation of their CNFs, and these were incorporated in the edible coatings. Edible coating formulations were based on blends of alginate (2% w/v), CNFs (0%, 0.1%, or 0.3%), glycerol, and water. In addition, stand-alone films were prepared, and their light and water vapor barrier properties were studied before applying the coating on the fruit surface. The results show that the addition of CNFs caused a significant decrease in the transparency and the water vapor permeability of the alginate films. After applying on the Andean blueberry fruits, the alginate and alginate/CNF coatings enhanced the appearance and the firmness of the fruits. Moreover, they significantly reduced the respiration rate and the water loss of the Andean blueberries throughout the 21 days of refrigerated storage. Alginate and alginate/CNFs coatings may be considered a useful alternative for the delay of the postharvest deterioration of Andean blueberries.